Deletion of rRNA Operons of Sinorhizobium fredii Strain NGR234 and Impact on Symbiosis With Legumes - Cherni, Ala Eddine; Perret, Xavier (Frontiers in Microbiology, 2019)
During their lifecycle, from free-living soil bacteria to endosymbiotic nitrogen-fixing bacteroids of legumes, rhizobia must colonize and cope with environments where nutrient concentrations and compositions vary greatly. Bacterial colonisation of legume rhizospheres and of root surfaces is subject to a fierce competition for plant exudates. By contrast root nodules offer to rhizobia sheltered nutrient-rich environments within which the cells that successfully propagated via infection threads can rapidly multiply. To explore the effects on symbiosis of a slower rhizobia growth and metabolism, we deleted one or two copies of the three functional rRNA operons of the promiscuous Sinorhizobium fredii strain NGR234 and examined the impact of these mutations on free-living and symbiotic lifestyles. Strains with two functional rRNA operons (NGRΔrRNA1 and NGRΔrRNA3) grew almost as rapidly as NGR234, and NGRΔrRNA1 was as proficient as the parent strain on all of the five legume species tested. By contrast, the NGRΔrRNA1,3 double mutant, which carried a single rRNA operon and grew significantly slower than NGR234, had a reduced symbiotic proficiency on Cajanus cajan, Macroptilium atropurpureum, Tephrosia vogelii and Vigna unguiculata. In addition, while NGRΔrRNA1 and NGR234 equally competed for nodulation of V. unguiculata, strain NGRΔrRNA1,3 was clearly outcompeted by wild-type. Surprisingly, on Leucaena leucocephala, NGRΔrRNA1,3 was the most proficient strain and competed equally NGR234 for nodule occupation. Together, these results indicate that for strains with otherwise identical repertoires of symbiotic genes, a faster growth on roots and/or inside plant tissues may contribute to secure access to nodules of some hosts. By contrast, other legumes such as L. leucocephala appear as less selective and capable of providing symbiotic environments susceptible to accommodate strains with a broader spectrum of competences.